Development of a support system for measurement and analysis of thinking processes based on a metacognitive interpretation framework: a case study of dissolution of belief conflict thinking processes - Yuki Hayashi; Kazuhisa Seta; Mitsuru Ikeda (The Asia-Pacific Society for Computers in Education (APSCE), 2018)
Abstract The ability for metacognitive thought, or "thinking about thinking," is recognized as an increasingly important skill for the future enrichment of social life. However, this skill is difficult to teach because it involves implicit cognitive activities that cannot be perceived by an outside observer. In this study, we propose an interpretation framework of metacognition as one approach to considering metacognitive thinking processes. This framework serves as the design principles for developing a system that makes it possible to provide metacognitive interpretations of gaze behaviors and thought operation actions and provides a common basis for sharing and comparing knowledge from analysis results. In this study, for an example of framework-based system development, we construct a thinking externalization application and thinking analysis support system with a thinking task of dissolving belief conflict as the theme. We also demonstrate an example of the analysis of thinking about belief conflict, as derived from lower-level and higher-level thinking interpretation rules. From the example results of the defined interpretation rules, we found that the desired behavior occurred, demonstrating the postulated possibility of capturing the thought process. By realizing a series of phases on the framework proposed in this paper, it contributes to the feasibility of grasping the metacognition process and accumulating knowledge about it.